1991
DOI: 10.1111/j.1399-3054.1991.tb02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Alanine aminotransferase in Leptosphaeria michotii. Isolation, properties and cyclic variations of its activity in relation to polypeptide level

Abstract: Alanine aminotransferase (EC 2.6.1.2) was obtained from the fungus Leptosphaeria michotii (West) Sacc, and enriched 714‐fold by a 5‐step purification procedure as a dimer of Mr 110000, associated with a polypeptide of Mr 25000. Its isoelectric point was 5.25. The enzyme was active from pH 3.5 to 9.5 with a maximum at pH 7.5. Its specific activity was 6000 nkat (mg protein)−1; the Km was 6.85 mM for L‐alanine and 0.2 mM for 2‐oxoglutarate. The enzyme did not show any detectable activity in the presence of L‐asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In the shoots of Scots pine seedlings, A1AT activity is regulated by light. These findings coincide with the results of studies using angiosperms (Hedley and Stoddart 1972;Biekmann and Feierabend 1982;Lillo 1984;Appenroth et al 1986;Abou-Zeid et al 1991;Penther 1991). They are also consistent with the notion that A1AT is a crucial enzyme for the re-assimilation of ammonium liberated during photorespiration (Joy 1988).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the shoots of Scots pine seedlings, A1AT activity is regulated by light. These findings coincide with the results of studies using angiosperms (Hedley and Stoddart 1972;Biekmann and Feierabend 1982;Lillo 1984;Appenroth et al 1986;Abou-Zeid et al 1991;Penther 1991). They are also consistent with the notion that A1AT is a crucial enzyme for the re-assimilation of ammonium liberated during photorespiration (Joy 1988).…”
Section: Discussionsupporting
confidence: 82%
“…Although it has been shown for several species that light causes an increase of A1AT activity (Hedley and Stoddart 1972;Biekmann and Feierabend 1982;Lillo 1984;Appenroth et al 1986;Abou-Zeid et al 1991 ;Penther 1991), the only systematic analysis of the influence of light on A1AT activity was performed by Penther (1991) with mustard (Sinapis alba L.) seedlings. It was shown that the activities of two isoforms (presumably both peroxisomal) were strongly increased by the operation of the phytochrome system.…”
Section: Introductionmentioning
confidence: 99%
“…When the level of asparagine is not sufficient to stabilize the period in darkness, continuous dim light permits a stable period, the length of which varies according to the irradiation level (Jerebzoff 1965;Jerebzoff et al 1969). The main component of the oscillating system, which controls the sporulation rhythm, is constituted by the asparagine-pyruvate pathway where 4 enzymes, asparaginase, aspartate and alanine aminotransferases, pyruvate carboxylase, express activity rhythms having a period identical with that of the S. Jerebzoff (corresponding author) and S. Jerebzoff (Jerebzoff and Jerebzoff-Quintin 1983a,b ;Abou-Zeid et al 1991 ;Tozo et al 1992). Two processes are involved in the control of the oscillating pattern of the asparagine-pyruvate pathway.…”
Section: Introductionmentioning
confidence: 97%
“…One of them regulates the asparaginase rhythm through changes in properties of the protein kinase and the protein phosphatase, which are associated with asparaginase in a complex (Jerebzoff-Quintin and Jerebzoff 1994). The other process regulates the rhythm of the mitochondrial aspartate aminotransferase isoform through translation of its mRNA (Romestant et al 1990) ; the same process could regulate the rhythms of alanine aminotransferase and pyruvate carboxylase since the cyclic variations of the activities are correlated with those of the enzyme levels (Abou-Zeid et al 1991;Tozo et al 1992).…”
Section: Introductionmentioning
confidence: 97%
“…The aspartate aminotransferase activity rhythm is caused by some mechanism specifically controlling the efficiency of translation of solely the mitochondrial isozyme (Romestant et al 1990). The cyclic variations of the activity of alanine aminotransferase, a cytosoiic polypeptide, are correlated with the cyclic variations in the enzyme levei (Abou-Zeid et al 1991), As far as we know, the cyclic activity of pyruvate carboxylase, another element of the asparagine-pyruvate pathway, had never been investigated.…”
mentioning
confidence: 99%